2017
DOI: 10.1002/2017ja024181
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Alfvén resonator and aurora: Modeling of MICA observations

Abstract: We present results from a numerical study of small‐scale, intense magnetic field‐aligned currents observed in the vicinity of the discrete auroral arc by the Magnetosphere‐Ionosphere Coupling in the Alfvén Resonator (MICA) sounding rocket launched from Poker Flat, Alaska, on 19 February 2012. The goal of the MICA project was to investigate the hypothesis that such currents can be produced inside the ionospheric Alfvén resonator by the ionospheric feedback instability (IFI) driven by the system of large‐scale m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…At the ionosphere, these currents can affect the Hall and Pedersen currents, hence the evolution of the IFI ultimately depends on the relative direction between the ionospheric electric field EI and the perpendicular wavevector k of the incident shear Alfven wave. Most of the theoretical studies of the IFI focused on a 2D geometry in which kEI: in this case, the feedback process could lead to the formation of parallel arcs at different latitudes (see for example the theoretical results by Atkinson, 1970; Miura & Sato, 1980; Pokhotelov, 2003 and the measurements reported by Lynch et al., 2015; Tulegenov & Streltsov, 2017), reminiscent of the Io tail splitting observed by Mura et al. (2018) far down the tail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the ionosphere, these currents can affect the Hall and Pedersen currents, hence the evolution of the IFI ultimately depends on the relative direction between the ionospheric electric field EI and the perpendicular wavevector k of the incident shear Alfven wave. Most of the theoretical studies of the IFI focused on a 2D geometry in which kEI: in this case, the feedback process could lead to the formation of parallel arcs at different latitudes (see for example the theoretical results by Atkinson, 1970; Miura & Sato, 1980; Pokhotelov, 2003 and the measurements reported by Lynch et al., 2015; Tulegenov & Streltsov, 2017), reminiscent of the Io tail splitting observed by Mura et al. (2018) far down the tail.…”
Section: Discussionmentioning
confidence: 99%
“…k E : in this case, the feedback process could lead to the formation of parallel arcs at different latitudes (see for example the theoretical results by Atkinson, 1970;Miura & Sato, 1980;Pokhotelov, 2003 and the measurements reported by Lynch et al, 2015;Tulegenov & Streltsov, 2017), reminiscent of the Io tail splitting observed by Mura et al (2018) far down the tail. In order to include an arbitrary direction of   E k a full 3D geometry have to be considered.…”
mentioning
confidence: 84%
“…The resonator can trap Alfvén waves by partial reflection at its boundaries, forming a standing wave pattern. Under favorable conditions, the trapped waves may become unstable to the Ionospheric Feedback Instability (IFI; Atkinson, 1970; Lysak & Song, 2002; Sato, 1978; Streltsov & Lotko, 2004; Tulegenov & Streltsov, 2017) and grow to large amplitudes where they can further modify the ionosphere via the current they carry or via the Ponderomotive force of their electric fields (Streltsov & Lotko, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A special, dedicated sounding rocket experiment, Magnetosphere‐Ionosphere Coupling in the Alfvén resonator, was conducted to verify that prediction in 2012. Results from the Magnetosphere‐Ionosphere Coupling in the Alfvén resonator experiment and numerical modeling are in a good quantitative agreement (Figure d; Tulegenov & Streltsov, ).…”
Section: Discussionmentioning
confidence: 58%
“…(C) Prediction of the frequencies of ULF waves used in active experiments at High frequency Active Auroral Research Program to initiate a substorm (from Streltsov et al ). (D) Prediction of the structure and location of small‐scale ULF waves observed in the vicinity of discrete arcs by the MICA sounding rocket flight (from; Tulegenov & Streltsov, ).…”
Section: Discussionmentioning
confidence: 99%